Inadequate Physical Activity and Health Care Expenditures in the United States - Carlson, Susan A.; Fulton, Janet E.; Pratt, Michael; Yang, Zhou; Adams, E. Kathleen (Progress in cardiovascular diseases, 2015)
This study estimates the percentage of health care expenditures in the non-institutionalized United States (U.S.) adult population associated with levels of physical activity inadequate to meet current guidelines. Leisure-time physical activity data from the National Health Interview Survey (2004–2010) were merged with health care expenditure data from the Medical Expenditure Panel Survey (2006–2011). Health care expenditures for inactive (i.e., no physical activity) and insufficiently active adults (i.e., some physical activity but not enough to meet guidelines) were compared with active adults (i.e., ≥150minutes/week moderate-intensity equivalent activity) using an econometric model. Overall, 11.1% (95% CI: 7.3, 14.9) of aggregate health care expenditures were associated with inadequate physical activity (i.e., inactive and insufficiently active levels). When adults with any reported difficulty walking due to a health problem were excluded, 8.7% (95% CI: 5.2, 12.3) of aggregate health care expenditures were associated with inadequate physical activity. Increasing adults’ physical activity to meet guidelines may reduce U.S. health care expenditures.